SIZE PERUSAHAAN MEMODERASI HUBUNGAN ENVIRONMENTAL PERFORMANCE, ENVIRONMENTAL DISCLOSURE DAN ISO 14001 TERHADAP FINANCIAL PERFORMANCE - Rohmah, Siti -; Suripto, Suripto -; Holiawati, Holiawati - (JURNAL ILMIAH EDUNOMIKA, 2024)
To date, the Indonesian Stock Exchange contunues to invite the public to make the Indonesian capital market an attractive and sustainable investment decision, by increasing investor awareness of the importance of running a sustainable bussiness, BEI anticipates that sustaunable aspect will become an important aspects will become an important factor in decision making. The objectives of this study are to test and analyze environmental performance, environmental disclosure, and ISO 14001 on financial performance, and  to test and analyze size firm in moderating environmental performance, environmental disclosure, and ISO 14001on financial performance. The method used in this study is a quantitative method where the data collection method used is saturated sample. Based on the results of the study, namely it is statistically proven that environmental performance has an effect on financial performance, but the environmental disclosure and ISO 14001 has not an effect on financial performance, it is statistically proven that size firm moderates the environmental performance with financial performance, but size firm doesn’t moderates the environmental disclosure and ISO 14001 with financial performance.